2022
DOI: 10.3390/agronomy13010024
|View full text |Cite
|
Sign up to set email alerts
|

Use of Biostimulants Obtained from Sewage Sludge for the Restoration of Soils Polluted by Diuron: Effect on Soil Biochemical Properties

Abstract: The use of biostimulants in the bioremediation of polluted soils in order to eliminate/reduce the toxic effects of pesticides on the soil is currently a very common environmental practice. In this study, we studied the bioremediation effect of three biostimulants obtained from sewage sludge by way of an enzymatic hydrolysis and fermentation process in a diuron-contaminated soil for 55 days under laboratory conditions. During this period of time, the enzymatic activities, bacterial community and the evolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Several authors have attempted to explain this decrease in the soil biochemical properties after the addition of a pesticide [6,16,28,31]. These authors observed decreases in biochemical properties and microbial biodiversity in soils contaminated with an oxyfluorfen herbicide or with chlorpyrifos and cypermethrin insecticides, suggesting that the inhibition of the biochemical properties of the soil is intimately related to the inhibition of microorganisms involved in the C, N, P and S cycle that are intolerant of, or susceptible to, the pollutant added to the soil as well as to the application dosage of said contaminant.…”
Section: Watered Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have attempted to explain this decrease in the soil biochemical properties after the addition of a pesticide [6,16,28,31]. These authors observed decreases in biochemical properties and microbial biodiversity in soils contaminated with an oxyfluorfen herbicide or with chlorpyrifos and cypermethrin insecticides, suggesting that the inhibition of the biochemical properties of the soil is intimately related to the inhibition of microorganisms involved in the C, N, P and S cycle that are intolerant of, or susceptible to, the pollutant added to the soil as well as to the application dosage of said contaminant.…”
Section: Watered Soilsmentioning
confidence: 99%
“…Urease, β-glucosidase, phosphatase and arylsulfatase enzymes are involved in the cycling of principal nutrients such as N, C, P and S [15]. Therefore, since such activities are commonly used in ecotoxicological tests to evaluate the behavior and influence of chemicals on soil systems, it may be useful to study them as early indicators of soil changes [6,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…To determine the microbial activity of the soil, the dehydrogenase enzymatic activity was used. This enzyme is related to oxidative phosphorylation, making it a good indicator of microbial activity (Tejada et al, 2023).…”
Section: Introductionmentioning
confidence: 99%